Analysis of IKM Plus Implementation in Measuring Public Satisfaction in Libraries in Central Java - Shanty Noor Mareta; Teguh Hardi Raharjo (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the implementation of the Community Satisfaction Index (CSI) Plus in measuring the level of public satisfaction with library services in Central Java. The background of the study is based on the important role of libraries as literacy centers in the digital era that is vulnerable to disinformation. The method used is a quantitative approach with data collection through questionnaires to library service users. The results show that the implementation of CSI Plus is able to provide a more comprehensive picture of service quality, including aspects of speed, comfort, accessibility, and staff competence. These findings indicate that improving the quality of library services contributes significantly to public satisfaction and encourages the improvement of literacy culture among the wider community in a sustainable manner.